Validation study of Boil & Spin Malachite Green Loop Mediated Isothermal Amplification (B&S MG-LAMP) versus microscopy for malaria detection in the Peruvian Amazon. - Keare A Barazorda (Public Library of Science (PLoS), 2021)
Malaria elimination efforts in Peru have dramatically reduced the incidence of cases in the Amazon Basin. To achieve the elimination, the detection of asymptomatic and submicroscopic carriers becomes a priority. Therefore, efforts should focus on tests sensitive enough to detect low-density parasitemia, deployable to resource-limited areas and affordable for large screening purposes. In this study, we assessed the performance of the Malachite-Green LAMP (MG-LAMP) using heat-treated DNA extraction (Boil & Spin; B&S MG-LAMP) on 283 whole blood samples collected from 9 different sites in Loreto, Peru and compared its performance to expert and field microscopy. A real-time PCR assay was used to quantify the parasite density. In addition, we explored a modified version of the B&S MG-LAMP for detection of submicroscopic infection in 500 samples and compared the turnaround time and cost of the MG-LAMP with microscopy. Compared to expert microscopy, the genus B&S MG-LAMP had a sensitivity of 99.4% (95%CI: 96.9%- 100%) and specificity of 97.1% (95%CI: 91.9%- 99.4%). The P. vivax specific B&S MG-LAMP had a sensitivity of 99.4% (96.6%- 100%) and specificity of 99.2% (95.5%- 100%) and the P. falciparum assay had a sensitivity of 100% (95%CI: 78.2%- 100%) and specificity of 99.3% (95%CI: 97.3%- 99.8%). The modified genus B&S MG-LAMP assay detected eight submicroscopic malaria cases (1.6%) which the species-specific assays did not identify. The turnaround time of B&S MG-LAMP was faster than expert microscopy with as many as 60 samples being processed per day by field technicians with limited training and utilizing a simple heat-block. The modified B&S MG-LAMP offers a simple and sensitive molecular test of choice for the detection of submicroscopic infections that can be used for mass screening in resources limited facilities in endemic settings nearing elimination and where a deployable test is required.